Long-Term and Institutional Care: A Global Perspective and Imperative - Kucharska, Katarzyna; Tabaszewski, Robert (Review of European and Comparative Law, 2023)
This study provides an overview of the legal aspects of long-term care (LTC) and institutional care for the elderly. It investigates whether LTC services for seniors could be recognized as a distinct human right, possibly through a United Nations convention. The study explores the existence and core components of the right to LTC and examines the minimum standards for its investigation, implementation, and enforcement. Additionally, it analyzes the specific rights of seniors that contribute to the right to care for dependent persons while also considering the intersectionality of this right and its relationship with other human rights. The study investigates the legal frameworks for protecting the right to LTC in various countries and assesses legal solutions derived from general legal instruments and special standards, particularly those concerning individuals with disabilities. Furthermore, it discusses proposed laws aimed at preserving the dignity of seniors and preventing unnecessary examinations and abuse. The study ultimately evaluates whether the right to LTC is an independent right or an extension of the rights to healthcare and social security.